Functional Outcomes Regarding Facial Artery Musculomucosal Flap for Reconstruction of Partial Glossectomy Defects. (July 2020) - Benjamin, Martin; Aliano, Kristen; Davenport, Thomas; Frank, Douglas
Abstract : Background: The surgical management and reconstruction after ablation of squamous cell carcinoma of the oral tongue and floor of mouth are quite challenging. If not reconstructed properly, the deficits resulting from the extirpation of even relatively small (T1 and T2) tumors of the tongue can impact speech and deglutition via tongue tethering and poor anterolateral mobility. Functional outcome studies regarding the utility of the pedicled facial artery musculamucosal (FAMM) flap for reconstruction of partial glossectomy defects are limited. Methods: This is a retrospective single institutional study of patients who underwent FAMM flap reconstruction for oral cavity defects resulting from partial glossectomy (2009–2013). Follow-up data included postoperative complications, defect size, operative time, and subjective functional results (tongue mobility, speech, and swallowing capabilities).The MD Anderson Dysphagia Inventory and a limited self-assessment of speech were sent to all living patients in this initial tongue cancer cohort to assess aspects of functional status. Results: Of the 21 patients studied in this initial FAMM flap cohort, 18 are currently living. The MD Anderson Dysphagia Inventory and a limited self-assessment survey of speech were sent to these individuals 6 months after treatment completion. Eight patients (44%) returned completed questionnaires. All of the respondents disagreed or strongly disagreed with the statement that they felt excluded from others because of their eating habits, 6 of the 8 of the respondents stated that they disagreed or strongly disagreed with the statement that they have to limit their food intake, and none felt that others were irritated by their eating habits. All felt that their speech was either good, very good, or excellent. No surveyed patient reported having job difficulty because of their speech. Conclusions: The FAMM flap is a reliable alternative for reconstruction of small oral tongue defects without functional deficits and a great alternative to free flap reconstruction of medium-sized defects. The encouragement of patient functional outcome studies and longitudinal follow-up studies need to be conducted in efforts to best tailor a reconstruction plan for patients with oral tongue cancers.